(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and Purpose: To compare the study between Kalternborn grade III mobilization and Muscle Energy Technique to increase range and functional ability in patients with mechanical neck pain. Design: Comparative study design. Methods: It is a pre and post- test Quasi experimental study, 30 patients between the age group of 18 to 40 years who comes under the inclusion criteria were selected Randomly and divided into 2 groups of 15 patients in each. First Group treated with Kalternborn grade III mobilization and second group with Muscle Energy Technique (METS). The period of study was 5 weeks. Pain and neck function were assessed before and after the treatment by Visual Analogue Scale and Neck Disability Index respectively. The collected data were valuated statistically. The study was calculated by Paired and Unpaired ‘t’ test. Conclusion: The study shows that the pain has been reduced & Neck function also improved among the patients who were treated with Kalternborn grade III mobilization to patients treated with Muscle Energy Technique (MET) for Mechanical Neck Pain. It is concluded that Muscle Energy Technique (MET) group shows statistical improvement in neck function.